Evaluation De L’impact De La Pollution Agricole Sur La Qualite Des Eaux Souterraines De La Nappe Du Gharb - Nouzha, Bouderka; Kacem, Souid Ahmed; Ferdaouss, Lakhili; Abrerrahim, Lahrach; Mohammed, Benabdelhadi (European Scientific Journal, ESJ, 2016)
The Gharb plain is located in the North West of Morocco and corresponds to a vast plain of the Sebou watershed. It includes an irrigable perimeter of a 250,000 ha, of which more than 120,000 ha are designed as big hydraulics to meet the drinking water and irrigation needs of the region. The intensification of agriculture in this region leads to a significant use of phytosanitary products, which can impact the physico-chemical quality of the Gharb groundwater. To assess this quality we proceeded to the analysis of the physico-chemical parameters (pH, electric conductivity, dissolved oxygen, chlorides, sodium, potassium, nitrates, ammonium, and orthophosphates) and the study of the metallic contamination of waters of 17 wells located in the region of Sidi Kacem-Sidi Slimane. The results of performed analysis, revealed a pollution of an agricultural origin. This is confirmed by the maximum levels of chlorides, which exceed 2,734 mg/l, thereby explaining the high conductivity levels (5000 μ/cm). Nevertheless, a lithological influence cannot be excluded. The nitrate levels (160 mg/l) indicate a nitric pollution of underground waters. The heavy metals measured showed a metallic contamination exceeding the norms of lead and aluminium concentration, elements which may have their origin in fertilizers undergoing an excessive use in the area. These results confirm the impact of the agricultural intensification in the degradation of the quality of the underground water of the Gharb region.